Banking in sub-Saharan Africa: Challenges and opportunities - Montfort Mlachila; Dennis Dykes; Sabina Zajc; Paul-Harry Aithnard; Thorsten Beck; Mthuli Ncube; Oskar Nelvin (European Investment Bank (EIB), 2013)
This study presents the macroeconomic context of sub-Saharan Africa and gives an overview of current developments and trends in the region's banking sector. In addition, it discusses challenges to and opportunities for further development of the sub-Saharan African banking sector, including the ones related to access to finance and infrastructure financing. – – In der Studie werden die makroökonomischen Bedingungen in afrikanischen Ländern südlich der Sahara erläutert und die aktuellen Entwicklungen und Trends im Bankensektor der Region im Überblick erörtert. Dabei gehen die Autoren auf die Herausforderungen und Chancen ein, die sich für den Bankensektor in diesen Ländern ergeben. Im Mittelpunkt stehen unter anderem der Zugang zu Finanzierungsmitteln und die Finanzierung von Infrastrukturvorhaben.
Keywords: 330